Iran and the Muslim World: Resistance and Revolution - Keddie, N. author. aut Link
X, 303 p.
Keywords: This book consists of a series of interrelated chapters analyzing why Iran, among all countries, has seen so many revolutionary movements in the past century; the degree to which its religion, Shi'ism, is revolutionary; and the history of revolutionary and resistance movements in the modern Muslim world. The author stresses historical change, such as the change of Twelver Shi'ism from political quietism to revolutionary opposition, and also previously unnoticed factors in revolution, such as the multi-urban character of all Iran's modern revolutions.